Conservation of Thermospermine Synthase Activity in Vascular and Non-vascular Plants - Solé-Gil, Anna; Hernández-García, Jorge; López-Gresa, María Pilar; Blázquez, Miguel A.; Agustí, Javier (Frontiers in Plant Science, 2019)
In plants, the only confirmed function for thermospermine is regulating xylem cells maturation. However, genes putatively encoding thermospermine synthases have been identified in the genomes of both vascular and non-vascular plants. Here, we verify the activity of the thermospermine synthase genes and the presence of thermospermine in vascular and non-vascular land plants as well as in the aquatic plant Chlamydomonas reinhardtii. In addition, we provide information about differential content of thermospermine in diverse organs at different developmental stages in some vascular species that suggest that, although the major role of thermospermine in vascular plants is likely to be xylem development, other potential roles in development and/or responses to stress conditions could be associated to such polyamine. In summary, our results in vascular and non-vascular species indicate that the capacity to synthesize thermospermine is conserved throughout the entire plant kingdom.